PENGUKURAN TINGKAT PARTISIPASI ANGGOTA DAN PENGARUHNYA TERHADAP KEBERHASILAN KOPERASI - Heri Nurranto; Firdaus Budhy Saputro (Universitas Indraprasta PGRI, 2015)
This analysis was based perspective that, success is strongly influenced by the quality of Cooperative Members Participation, then by analyzing the factors underlying the Member Participation, the cooperative has special attention to what variables can stimulate members to take advantage of the products and the existence of cooperatives as a form of participation. Next, we tested the integrative model consisting of Member aspect, Cooperative Management, Program Participation, Quality of Participation and success of cooperatives. This model is used to test the hypothesis that we submitted. Data were collected through questionnaires from 108 Members Kopkar Unindra, where the results of the calculation software SmartPLS prove that Member aspect significant positive effect on quality of Member Participation by the value of the beta coefficient of 0.5396, t-value of 5.2487. Management Cooperative positive effect on the quality of the Member Participation beta coefficient 0.1899, t-value of 2.269. Program Participation positive effect on the quality of the Member Participation beta coefficient t-value 0.1523 and 1.6701 and Quality Member Participation positive effect on the success of the cooperation with 0,4934.dan beta coefficient t-value of 5.9336. R-square on the construct of Quality of Member participation in the structural model of 0.4879, meaning that Member aspect, Cooperative Management and Program Participation jointly able to explain the construct of Quality of Member participation of 48.79%. While the success of the Cooperative construct has a coefficient R-square of 0.2434 means that the construct Quality Member Participation able to explain the success of the Cooperative constructs of 24.34%.Keywords: Participation and Success Cooperative Members